(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
During adolescence, our bodies undergo physiological and biological changes. Hormonal changes also begin during this period. The hormones FSH and LH, which are released from the pituitary gland, begin to stimulate the ovaries, and menstruation begins with the effect of female hormones on the lining of the uterus. In other words, a woman produces eggs every month.